Paraneoplastic Mononeuritis Multiplex as a Presenting Feature of Adenocarcinoma of the Lung - Esra Ekiz; Abdullah Ozkok; Nazan Kader Ertugrul (Case Reports in Oncological Medicine)
Paraneoplastic neurologic syndromes are observed in less than 0.1% of cancer patients. Neurologic syndromes in lung cancer include Lambert-Eaton myasthenic syndrome, polyneuropathy, cerebellar degeneration, and rarely mononeuritis multiplex. In this case, a patient presenting with bilateral asymmetrical sensorimotor polyneuropathy who was diagnosed with adenocarcinoma of the lung is reported.